Occurrence and removal of potentially toxic metals and heavy metals in the wastewater treatment plant of Fusina (Venice, Italy) - Busetti, Francesco; Badoer, S.; Cuomo, M.; Rubino, B.; Traverso, P. (American Chemical Society, 2005)
This study addresses the issue of whether it is possible to accurately predict the removal efficiencies of metals of environmental concern (i.e., Al, Ag, As, B, Ba, Cd, Cr, Fe, Mn, Hg, Ni,Pb, Cu, V, and Zn) in a wastewater treatment plant. The plant in question (at Fusina, Venice, Italy) is fed by mixed wastes from municipal and industrial sources (300 000 equivalent inhabitants) and discharges the treated effluent into the Venice lagoon. The year-long sampling campaign (2001-2002) yielded a substantial amount of analytical data and relatively wide ranges of concentrations of metals in the influent samples, which made it possible to study the removal efficiencies by plotting the terms (inlet concentration - outlet concentration) vs (inlet concentration) for each metal investigated. The data in the plots were fitted using the linear regression model Y ) BX. The slope rates (terms B), which were estimated by the least-squares method, have been adopted as the removal efficiencies, and they can be considered as constants in the concentration ranges recorded in this work. The relative abundance of metals in the raw wastewaters feeding Fusina WWTP followed the order Al > Fe > B > Zn > Ba > Mn > Cu > Pb > Hg = Ni > Cr = As > V > Ag > Cd, while in the effluent the order was Fe > Al > Zn > Mn > Ba > Ni > Cu > Pb > Cr > Ag > As > Hg = V > Cd. The removal percentages (%) of the metals were Al = 92 ± 1; Ag = 94 ± 1; As = 76 ± 3; B = n.d.; Ba = 85 ± 2; Cd = 85 ± 2; Cr = 87 ± 1; Fe = 90 ± 1; Mn = 61 ± 2; Hg = 93 ± 1; Ni = 50 ± 3; Pb = 92 ± 1; Cu = 93 ± 1; V = 74 ± 2; and Zn = 75 ± 3.